Secondary mania following cancer chemotherapy with capecitabine. (28th March 2018) - Garg, Harshit; Prakash, Sathya; Deb, Koushik Sinha; Chadda, Rakesh Kumar
Abstract : Mania-like states occurring due to neurological, metabolic or toxic conditions, without a primary mood disorder have been reported in scientific literature as secondary mania. A major clinical problem in such situations often stems from the difficulty to understand if the mood disturbance is indeed secondary to an organic cause or a coincidental primary mood disorder. Chemotherapy regimens have been associated with multiple psychiatric complications, including psychosis, mania and anxiety. Capecitabine is implicated to be associated with encephalopathy whose clinical presentation often mimics that of psychosis. However, presentations with mania have not been reported until with the capecitabine and oxaliplatin combination chemotherapy regimen. In this report, we describe a case of secondary mania in a patient suffering from carcinoma colon on treatment with chemotherapy regimen of capecitabine and oxaliplatin.